Effectiveness of Ketoprofen Suppositoria as Preemptive Analgesia for Postoperative Pain in Patients Undergoing Elective Surgery with General Anesthesia - Lupi Lestari; Elizeus Hanindito; Arie Utariani (Indonesian Journal of Anesthesiology and Reanimation, 2020)
Introduction: Effective postoperative pain management provides improved patient comfort and satisfaction, earlier mobilization, fewer pulmonary and cardiac complications, reduced risk deep vein thrombosis, fast recovery, and reduced cost of care. Preemptive analgesia, initiated before the surgical procedure to prevent pain in the early postoperative period, has the potential to be more effective than a similar analgesic treatment initiated after surgery. As a part of multimodal analgesia, the use of NSAIDs should always be considered for acute postoperative pain management. NSAIDs can be used preoperatively as a part of the preemptive regimen and for postoperative pain control to increase the efficacy of opioids and reduce its side effects. Material and Method: This research was experimental research with a case-control design of the study. The samples separated into two groups, the first group got ketoprofen suppository before the induction, and the second group didn't get the ketoprofen suppository The intensity of pain measured with the Numeric Rating Scale (NRS) or Wong-Baker Faces Pain Scale was the variable studied at different postoperative times (30 min, 60 min, 120 min, 2-6 hours, 6-12 hours). The total amount of rescue analgesics (fentanyl) and side effects were other variables of this study. Result and Discussion: The result is ketoprofen suppository as preemptive analgesia administrations can reduce postoperative pain. Numeric Rating Scale was significantly lower in the ketoprofen group compared to the control group (p < 0,05) at 30 min, 60 min, 230 min, 2-6 hours, 6-12 hours. The number of postoperative analgesics needed in the recovery room was significant differences among both groups (p < 0,05). Conclusion: Preemptive analgesia in patients who underwent an operation with general anesthesia with ketoprofen suppository was effectively in blocking noxious stimuli and central sensitization, with subsequent prevention of acute postoperative pain.